Exploring fishers’ and fisherfolk’s knowledge and perspectives on water pollution in India: insights from Chilika Lake - Mengo, Elena; Murali, Rashmi; Govindan, Mini; Hoehn, Danja (Frontiers in Sustainable Food Systems, 2025)
Approximately 16 million fisherfolk in India depend on fisheries for their income, food, and nutritional security. However, aquatic ecosystems across India are heavily polluted, resulting in significant challenges for communities dependent on fisheries. While research on pollution and waste management in India has progressed, local coastal communities’ knowledge and perspectives are still overlooked in environmental decision-making. To address this gap, we focused on the Chilika Lake area, employing a mixed-method approach. We surveyed 161 fishers and conducted focus group discussions (FGDs) in local communities. Our findings indicate that, although fisheries serve as the primary source of livelihood, water pollution adversely affects the quantity and quality of fish, ultimately impacting the household income. Tourism and agriculture, including aquaculture are considered major contributors to aquatic pollution. While fishing-related litter does contribute to pollution in coastal areas, fishers infrequently encounter derelict gear compared to plastic bags and bottles. Solid waste disposal and management issues are widespread, largely due to inadequate waste collection and disposal facilities, resulting in the prevalence of informal waste management systems. The outcomes of the research highlight the need for targeted education and outreach initiatives in coastal areas to address waste mismanagement, promote active participation among local communities to initiatives such as beach clean ups, as well as encourage practices of recycling and reusing materials. Similarly, developing alternative livelihoods can reduce dependency on fisheries and contribute to sustainable development and biodiversity conservation.